2014
DOI: 10.1097/md.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Uses of Cervical Vestibular-Evoked Myogenic Potential Testing in Pediatric Patients

Abstract: To demonstrate the feasibility and clinical significance of cervical vestibular-evoked myogenic potential (cVEMP) test in pediatric patients.Retrospective review study was conducted in a pediatric tertiary care facility. A total of 278 patients were identified with adequate data, including medical notes, results of cVEMP, and imaging studies.Among the total of 278 pediatric patients, only 3 children were not able to finish the cVEMP test successfully. In about 90% of the cases, the cVEMP test was requested to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
(25 reference statements)
1
16
0
1
Order By: Relevance
“…When the extensive protocol for older children is considered, the caloric test remains the most challenging, reaching higher success rates as the child grows older. Consistent with the consensus in literature, the highest success rates for the vestibular‐evoked myogenic potentials demonstrate that these are the most feasible vestibular tests in the pediatric population . The relatively new vHIT is also promising, as it is fast, child friendly, easy to conduct, and it provides ear‐specific information about the semicircular canal system.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…When the extensive protocol for older children is considered, the caloric test remains the most challenging, reaching higher success rates as the child grows older. Consistent with the consensus in literature, the highest success rates for the vestibular‐evoked myogenic potentials demonstrate that these are the most feasible vestibular tests in the pediatric population . The relatively new vHIT is also promising, as it is fast, child friendly, easy to conduct, and it provides ear‐specific information about the semicircular canal system.…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with the consensus in literature, the highest success rates for the vestibular-evoked myogenic potentials demonstrate that these are the most feasible vestibular tests in the pediatric population. 13 The relatively new vHIT is also promising, as it is fast, child friendly, easy to conduct, and it provides ear-specific information about the semicircular canal system. Despite its noninvasive character, success rates of vHIT are still lower compared to vestibular-evoked myogenic potentials tests.…”
Section: Discussionmentioning
confidence: 99%
“…Another method to reduce sound exposure secondary to VEMP is to employ the use of a bone-conduction stimulus. While less is known about the effects of safety in performing bone conduction VEMP testing (Papathanasiou et al 2014), the use of bone vibration (e.g., minishaker, reflex hammer tap) has been performed in adults (Halmagyi et al 1995; Nguyen et al 2010; Rosengren et al 2011; Wackym 2012;) and children (Monobe & Murofushi 2004; Zhou et al 2014) with advantages. For one, bone conduction VEMP responses have been shown to be more reliable and robust than air-conduction responses (Brantberg et al 2003; Cheng et al 2009; Wackym et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that latencies and amplitudes will be less than in the adult population (35). Zhou et al (36) studied VEMPS in children and observed that in inner ear structural abnormalities (for example enlarged vestibular aqueduct and semicircular canal dehiscences), VEMPs have lower thresholds and increased amplitude as one would expect in adults. However, it is not clear from this study as to what is defined by a structural inner ear abnormality.…”
Section: Discussionmentioning
confidence: 99%